Exacerbation of immune thrombocytopenia following initial and booster vaccination with Pfizer-BioNTech COVID-19 vaccine. (4th July 2022) - Aharoni, Maayan; Leader, Avi; Shochat, Tzippy; Raanani, Pia; Spectre, Galia
Abstract: As the immune thrombocytopenia exacerbation rate after booster COVID-19 vaccines is unknown, we explore the rates after first, second and booster Pfizer-BioNTech COVID-19 vaccines. A retrospective study of adult ITP patients, receiving 1–3 vaccines was performed. The primary outcome was clinical ITP exacerbation defined as platelet count decrease requiring initiation/escalation of ITP treatment and/or new medical attention due to bleeding, within 3 months. Secondary outcome was any clinically relevant platelet decrease during the 3 months post-vaccination. The study included 93 ITP patients receiving 1 (n = 2), 2 (n = 22) or 3 (n = 69) vaccines. ITP exacerbation occurred in 2/93 (2.2%) patients following initial vaccination and in 3/69 (4.3%) following booster dose. Clinically relevant platelet decreases after initial doses occurred in 8/72 (11.1%) patients and in 8/39 (20.5%) after the booster. Clinical ITP exacerbation after booster doses did not follow clinical exacerbation after initial doses. Half of patients with clinically relevant platelet decreases after booster dose also had clinically relevant decreases following initial vaccination. We concluded that clinical ITP exacerbation is infrequent following Pfizer-BioNTech COVID-19 vaccine. Clinical exacerbation after booster doses was not preceded by clinical exacerbation after initial doses. Clinically relevant platelet decreases after booster doses occur frequently in patients with clinically relevant decreases after initial doses.